Survival of melanopsin expressing retinal ganglion cells long term after optic nerve trauma in mice. (September 2018) - Sánchez-Migallón, M.C.; Valiente-Soriano, F.J.; Nadal-Nicolás, F.M.; Di Pierdomenico, J.; Vidal-Sanz, M.; Agudo-Barriuso, M.
Abstract: In this study we have compared the response to optic nerve crush (ONC) and to optic nerve transection (ONT) of the general population of retinal ganglion cells in charge of the image-forming visual functions that express Brn3a (Brn3a + RGCs) with that of the sub-population of non-image forming RGCs that express melanopsin (m + RGCs). Intact animals were used as control. ONT and ONC were performed at 0.5 mm from the optic disk, and retinas dissected 3, 5, 7, 14, 30, 45 or 90 days later (n = 5/injury/time point). In all the retinas, Brn3a + RGCs and m + RGCs were identified and their survival analyzed quantitatively and topographically. There were no differences in the course of RGC loss between lesions. The decrease of RGCs was significant at short time points (3 or 5 days for Brn3a + or m + RGCs, respectively) and, up to 14 days, the course of loss of both RGC populations was similar, surviving at this time point between 20 and 22% of their original population. However, while the loss of Brn3a + RGCs continues steadily up to 90 days when only 5–6% of them still remain, the loss of m + RGCs stops at 14 days, and the proportion of surviving m + RGCs remains constant up to 90 days (26–30%). In conclusion, m + RGC do not respond to axotomy in the same way than the rest of RGCs, and so whilst image-forming RGCs die in two exponential phases a quick one and a slow protracted one, non-image forming RGCs die only during the first quick phase. Highlights: In mice, optic nerve transection and crush trigger the same course of RGC loss. Melanopsin + and Brn3a + RGCs loss is similar during the quick phase of death. Melanopsin + RGCs loss after axotomy stops at 14 days. Proportionally, more melanopsin + than Brn3a + RGCs survive long term after axotomy.